Wildlife detection dogs effectively survey a terrestrial amphibian, but differ among individuals, weather and habitat - Veronika Paulina Koch; Leonard Bolte; Wiebke Harms; Klaus Henle; Annegret Grimm‐Seyfarth (Ecological Solutions and Evidence, 2025)
Abstract The endangered natterjack toad (Epidalea calamita) faces ongoing habitat loss, requiring effective conservation measures. Field surveys must therefore address its highly variable detectability in terrestrial habitats. We investigated the factors influencing capture success comparing two methods: artificial cover boards (ACBs) and wildlife detection dogs (WDDs). We first analysed environmental and training factors influencing toad detectability for four detection dogs with varying experience using a binomial generalized linear model (GLM). Then, we compared capture success of ACBs and WDD transects (deploying two dogs) considering weather and habitat type using negative binomial GLMs. Across 200 tests, each detection dog displayed a unique learning curve, with performance influenced mainly by dog behaviour, wind, test blindness and insect presence. Detection rates across dogs levelled off at 87.2% (75.7%–94.8%). Capture success of both methods under real‐deployment conditions was separately analysed for juvenile and (sub‐)adult toads by calculating a success rate. For juvenile toads, capture success was primarily influenced by capture method, habitat type and study year, while adult toads capture success mainly depended on habitat type and precipitation. Overall, WDDs (mean rate juvenile toads = 4.15, mean rate adult toads = 5.61) showed higher success rates than ACBs (mean rate juvenile toads = 0.51, mean rate adult toads = 4.73), particularly in dense and versatile habitats. Practical implication. This study provides practical guidance for the selection and implementation of survey methods for E. calamita, identifying critical factors to consider when designing a study to maximize survey success. Dog handlers should be able to adapt search and training strategies to their dogs' individual pace and limitations and keep environmental influences in mind. Both ACBs and WDDs are suitable methods for detecting E. calamita in terrestrial habitats; however, detection dogs are particularly useful in densely vegetated areas, for finding juveniles and for covering larger regions more efficiently. Success rates for adult toads increase in favourable habitat and climatic conditions, such as warmer temperatures and sufficient moisture. Our findings provide a framework that may be extended to the monitoring and conservation of other amphibian species.